PROMOSI PEMASARAN UNTUK MENINGKATKAN DAYA SAING DI MADARASAH TSANAWIYAH TARBIYAH ISLAMIYAH KOTA JAMBI - Nurjanah, Tri; Maisah; Sya’roni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze educational marketing promotion in improving competitiveness at Madrasah Tsanawiyah Tarbiyah Islamiyah, Jambi City. The research is motivated by the intense competition among educational institutions in the digital era, which requires madrasahs to implement effective and adaptive promotional strategies. This study employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving the principal, vice principals, teachers, parents, students, and the community. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity ensured through triangulation. The findings indicate that marketing promotion has been carried out through conventional and digital media, such as brochures, banners, word-of-mouth promotion, and social media. However, the implementation has not been optimal due to limited human resources, inadequate digital-based promotional planning, and suboptimal management of promotional media. Supporting factors include leadership commitment, strategic location, and the Islamic identity of the institution, while inhibiting factors include limited budget and lack of digital marketing skills. Efforts to enhance competitiveness are carried out by strengthening the institutional image, improving the quality of educational services, and developing digital promotion based on Islamic values.